Effectiveness of Red Onion (Allium cepa L.) Ointment in Reducing Pain Intensity and Salivary Cortisol Levels Among Adolescent With Primary Dysmenorrhea - Clara Tika Pangesti; Sri Sumarni; Marsum Marsum (Poltekkes Kemenkes Yogyakarta, 2026)
Primary dysmenorrhea is a common condition among adolescent girls that substantially impairs daily functioning and quality of life, with prevalence reaching 87.8% in Semarang. This study aimed to evaluate the effectiveness of red onion ointment in reducing pain intensity and salivary cortisol levels among adolescents with primary dysmenorrhea. A randomized pretest–posttest-controlled trial group design was conducted involving 36 participants, who were randomly allocated using computer-generated simple randomization into an intervention group (n=18) and a control group (n=18). The intervention group received 2 grams of red onion ointment twice daily during the first three days of menstruation, while the control group received heat cream. Pain intensity was assessed using the Numeric Rating Scale, and salivary cortisol concentration was analyzed in the laboratory. Baseline pain intensity was comparable between groups, whereas baseline salivary cortisol concentration differed significantly. After the intervention, the red onion ointment group showed significantly greater reductions in Δ pain score (3.33±0.49 vs. 0.50±0.51) and cortisol (3.61±2.19 vs. 0.43 ± 3.78) compared with control (p<0.001). Effect sizes were very large for pain (d=5.67) and large for cortisol (d=1.03). These findings demonstrate that red onion ointment effectively reduces primary dysmenorrhea pain and physiological stress. It may serve as a promising complementary therapy although further studies are needed to evaluate long-term safety and broader applicability.